Sirna kaplı ipliklerin neointimal hiperplaziyeetkilerinin araştırılması - Çanak, Tuba (My University, 2015)
Amaç: Neointimal hiperplazi, koroner arter baypass ameliyatlarından ve diğer damar endoteli operasyonlarından sonra ortaya çıkan çok ciddi bir sorundur. Platelet türevi büyüme faktörünün (PDGF) farklı tiplerinin (AA, BB, C ve D) tirozin kinaz reseptörlerine (á ve â) bağlanarak arteriyal intimal hiperplaziyi stimule ettiği bilinmektedir. Diğer yandan epidermal büyüme faktörünün hücre proliferasyonunda rol aldığı ve vasküler düz kas hücrelerinin EGF eksprese ettiği de bilinmektedir. Bu çalışmada amaç; PDGF-D ve EGF’in baskılanarak neointimal hiperplazinin oluşumunu engellemek için kitozanla hazırlanan komplekslerin in vitro etkisini araştırmaktır. Gereç ve Yöntem: siEGF, siPDGF-D, insan umbilikal ven endotel hücre hattı (HUVEC), kitozan (farklı moleküler ağırlıkta), 3 farklı tip cerrahi iplik, PDGF-D/ EGF ELISA kitleri kullanılmıştır. Kitozan/ siRNA kompleksleri oluşturularak iplikler hazırlanan komplekslerle kaplanmıştır. Kaplı ipliklerin in vitro salım ve gen inhibisyonu özellikleri incelenmiştir. Bulgular: Kitozan/ siRNA tam kompleks oluşumu başarılı bir şekilde sağlanmıştır. Cerrahi iplikler bu komplekslerle kaplanmış, kaplı ipliklerin in vitro salım grafikleri oluşturuldu ve in vitro transfeksiyon sonucunda gen inhibisyonu yüzdeleri hesaplandı. Sonuçlar: PDGF-D ve EGF hedefli Kitozan/ siRNA kompleksleri ile (50:1) kaplanan ipliklerin in vitor hücre kültüründe HUVEC hücre hattında PDGF-D ve EGF ekspresyonunu sırası ile % 47,40 % 47,82 oranında azalttığı saptandı. Anahtar Sözcükler: siRNA, kitozan, neointmal hiperplazi, kaplı iplik, PDGF-D/ EGF Investigation the effect of of siRNA Coating Suture on Neointimal Hyperplasia

Aim: Neointimal hyperplasia is a serious problem that generally occurs after coronary artery bypass and other vascular endothelium operations. It is known that different types of platelet-derived growth factors (PDGF-AA, -BB, -C and -D) stimulated arterial intimal hyperplasia by attaching tyrosine kinase receptors (á and â). Although there are many studies about A, B and C, PDGF-D is a new target for inhibition of vascular restenosis developed after coronary angioplasty. On the other hand, epidermal growth factor (EGF) is a 6,21 kDa polypeptide that is expressed by vascular smooth muscle cells. The aim of this study is to investigate in vitro effects of chitosan/ siRNA complexes to prevent the neointimal hyperplasia with inhibition of PDGF-D and EGF. Material and Methods: siEGF, siPDGF-D, human umbilical vein endothelial cell line (HUVEC), chitosan (different molecular weights), different surgical sutures, PDGF-D/ EGF ELISA kit Chitosan-siRNA complexes were prepared and then sutures were coated with the complexes. Coated sutures were used for in vitro transfection, release and cell proliferation studies after quality controls. Results: Chitosan/ siRNA complexes were formed and then surgical sutures were coated with these complexes. Release profile of coated sutures was observed and gene inhibition was calculated after in vitro transfection. Conclusion: Sutures were coated with PDGF-D and EGF targeted chitosan siRNA complexes (50:1), coated sutures were controlled. It was observed that coated sutures inhibited PDGF-D and EGF gene expression in HUVEC cell line. Key Words: siRNA, chitosan, neointimal hyperplasia, coating suture, PDGF-D/ EGF
Keywords: Farmasötik biyoteknoloji; Farmasötik Çalışmalar; Pharmaceutical Aids; Pharmaceutical biotechnology